1996
DOI: 10.1038/sc.1996.17
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of pudendal nerve electrical stimulation on detrusor hyperreflexia in spinal cord injury patients: importance of current strength

Abstract: Twenty patients with chronic supra sacral spinal cord injury presenting with detrusor hyperreflexia were examined. In a preliminary study in ten patients we investigated the reproducibility of bladder capacity through the repetition of three cystometries. The effect of electrical stimulation (ES) on detrusor hyperreflexia was then investigated in ten patients during three consecutive cystometries, the first one without ES (baseline) and the other two with continuous ES of the dorsal penile or clitoris nerve vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 19 publications
2
51
1
1
Order By: Relevance
“…The rise in bladder volume during the three initial control ®lls in our six patients was signi®cant ± this e ect has been noted before. 24,25 The persisting (but diminishing) e ect following neuromodulation in the ®nal control ®lls has also been found before, 7,8 and was probably due to two main factors. Firstly, an initial mechanical distension is likely to diminish a erent discharge from the bladder at a given volume during subsequent ®lls; such an e ect has been shown directly in cats.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The rise in bladder volume during the three initial control ®lls in our six patients was signi®cant ± this e ect has been noted before. 24,25 The persisting (but diminishing) e ect following neuromodulation in the ®nal control ®lls has also been found before, 7,8 and was probably due to two main factors. Firstly, an initial mechanical distension is likely to diminish a erent discharge from the bladder at a given volume during subsequent ®lls; such an e ect has been shown directly in cats.…”
Section: Discussionsupporting
confidence: 53%
“…One group has speci®cally examined the in¯uence of current strength on bladder suppression, achieving their best results at twice the threshold and markedly reduced suppression when stimulating at a level equal to the threshold. 24 In the current study, the pudendo-urethral re¯ex had a lower threshold than the pudendo-anal re¯ex in a majority of patients, a point which should be borne in mind if using it to set the current level for neuromodulation.…”
Section: Conditional Neuromodulationmentioning
confidence: 58%
“…The stimulation amplitude of the pulse train stimulation during bladder filling was not related to the threshold for the GAR, as the GAR could not effectively be evoked with pulse train stimulation in the majority of patients. Previnaire et al 12 showed that continuous stimulation (bipolar surface electrodes, rectangular pulse, 5 Hz, pulse width 500 ms) at twice the GAR threshold increases bladder capacity more than does a stimulus at one times the threshold (mean 24.2 mA, range 14.0-40.0 mA). Although our study did not assess capacity, and stimulation parameters were different, it also demonstrated the importance of amplitude on IDC suppression.…”
Section: Discussionmentioning
confidence: 99%
“…This eect is observed in normal subjects, 1 idiopathic bladder instability, 2 and in the detrusor hyperre¯exia that is the likely consequence of spinal cord injury. 3 It can be termed neuromodulation, where`the in¯uence of activity in one neural pathway aects the pre-existing activity in another by synaptic interaction.…”
Section: Introductionmentioning
confidence: 99%